The Vestibular System in Cognitive and Memory Processes in Mammals - Thomas Brandt (Frontiers Research Topics, 2016)
Since the beginning of life, all plant and animal kingdoms have been developed or modified based on gravity along with atmospheric composition and solar radiation existing on Earth. Gravity is mainly encoded by the otolithic sensors of the vestibular system but its role has been largely underestimated in favor of the vestibular semicircular canals and reduced to oculomotor and postural coordination. Over the last decade, it has been demonstrated that sensory information provided by the vestibular system is crucial in spatial-memory processes in rats and humans. More recently a role in attention processes has been raised. This topic aims to report and demonstrate the role and integration of vestibular information in cognitive processes in rodent models and human at the behavioral, imaging and electrophysiological levels.